Comparison of Organizational Structures of the Baduy and Banten Kidul Indigenous Communities and Their Impact on Community Satisfaction Based on the Community Satisfaction Index - Pranamulia, Agus; Putra, Mulyana Gustira (Jurnal EMT KITA, 2026)
This study represents a truly novel discovery in comparing the organizational structure of indigenous communities and its impact based on the community satisfaction index (invention novelty). The Baduy and Banten Kidul indigenous communities inhabiting Banten Province have consistently struggled for years to gain recognition and protection of their cultural identity, religion, way of life, rights to land, territory, and natural resources. Therefore, they need to strengthen their organizational structure, which is a product of local wisdom to realize their vision, mission, goals, strategies, and programs in expanding public services. The purpose of this study is to compare the organizational structures of the two and their impact on community satisfaction. A sample of 150 people was taken using a non-probability incidental sampling technique, namely anyone from the indigenous community who happened to meet the researcher and was deemed suitable as a data source. The method used in this study is a mixed method of qualitative and quantitative with a descriptive approach.  The results of the study show that in practice, the organizational structure of the Baduy and Banten Kidul indigenous communities has similarities in terms of 1) centralistic leadership; 2) having the task of maintaining and protecting the Balance of Nature; 3) using informal communication, direct supervision, formal hierarchy, and standardization; and 4). While the differences lie in: 1) vertical hierarchy; 2) span of control; 3) organizational form; behavior towards environmental influences; and mechanisms in selecting Village Heads. Various aspects in the dimensions of organizational structure, especially those related to leadership and organizational form have a significant impact on satisfaction. The organizational structures of both resulted in indigenous community satisfaction with the quality of service being Very Good (99.4 = A) in Baduy and Good (79.6 = B) in Banten Kidul.